Traveling Planetary Waves in Ozone Layer over Antarctic Peninsula - Grytsai, A.V.; Grytsai, Z.I.; Evtushevsky, A.M.; Milinevsky, G.P.; Leonov, N.A. (Національний антарктичний науковий центр МОН України, 2004)
Preliminary results of the analysis of the traveling planetary wave evolution in the ozone layer over the region of Antarctic Peninsula are presented. Total ozone data obtained at the Vernadsky station and TOMS satellite measurements are used. The main characteristics of the traveling waves, namely the spectral distribution, period, amplitude and velocity were considered. At the station latitude of 65.25°S the amplitude of the traveling wave number 2 becomes equal or exceeds the stationary wave number 1 amplitude in individual cases only. In average for the period 1979-2003 the relationship of amplitudes of the wave numbers 1, 2, 3, 4 and 5 is 1, 0.56, 0.29, 0.19, and 0.15. The wave periods 6-8 and 10-12 days are dominant. Velocities of 8-10 m/s are obtained.